Legal Protection of Creditors in Credit Agreements with Warranties of Power of Attorney Impose Collateral Rights That Have not Been Registered Based on PMA/KBPN NUMBER 22 of 2017 at Pt. BPR Harta Mandiri Pekanbaru - Reza Azurma; Yulfasni Yulfasni; Syahrial Razak (West Science Law and Human Rights, 2023)
Encounter rapidly growing, competitive, and integrated national economic development with increasingly complex challenges and an increasingly advanced financial system that requires policy adjustments in the economic field, including banking. Economic recovery is inseparable from the banking business's hazardous credit distribution. Therefore, collateral is significant in the issuance of credit. In practice, the Bank as a creditor provides credit facilities to the debtor. SKMHT was made to become a basis for making a Deed of Mortgage Rights (APHT). However, SKMHT has a term. Thus, both the creditor and the notary / PPAT must pay serious attention to the validity period because the expired SKMHT affects the APHT cannot be registered, so the Bank cannot execute the debtor's default guarantee object. The problems in this study are the factors that affect creditors in credit agreements with SKMHT guarantees that cannot register their rights and how to protect creditor law in credit agreements with SKMHT guarantee based on PMA / KBP Number 22 of 2017. The research method used is juridical-empirical and descriptive analysis, then analyzed qualitatively. Banks in credit binding only limited SKMHT as a bridge to make APHT. When SKMHT cannot be increased to APHT, the Bank cannot execute the guarantee object in the credit agreement. The factors that influence SKMHT cannot be upgraded to APHT because the Bank gives credit on specific credit based on the PMA / KBPN Number 22 of 2017, the process of registration of the mortgage is too long, negligent Notary / PPAT considering the expiry of SKMHT period so that the legal protection that can be done is by filing a civil suit at the local District Court with evidence of the binding of credit agreement between the Bank and the debtor. So that the object of the collateral can be executed.